Bat and the Waiting Game - Arnold, Elana K.; Santoso, Charles (New York, NY Walden Pond Press, an imprint of HarperCollinsPublishers, 2018)
When Bats older sister Janie gets a part in the school play, and cant watch him after school, it means some pretty big changes. For one, someone else will have to take care of the skunk kit in the afternoons.
Keywords: Autism -- Juvenile fiction; Skunks as pets -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Friendship -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Autism -- Fiction; Skunks as pets -- Fiction; Brothers and sisters -- Fiction; Friendship -- Fiction; Human-animal relationships -- Fiction